Man-made soil drainage alters the vegetation structure and woody species distribution in campo de murundus - Guimarães Guilherme, Frederico Augusto; Soardi Maricato, Hortência; Marimon, Beatriz Schwantes; Pereira, Firmino Cardoso; Souza, Luzia Francisca de; Coelho, Christiano Peres; Ferreira, Wendy Carniello; Ferreira Júnior, Angélica; Pereira, Kaila de Assis Ressel (Acta Scientiarum. Biological Sciences, 2020)
Campos de murundus work as recharge zones and are important for the maintenance of water resources in Brazilian Cerrado. However, with the expansion of the agricultural frontier, this ecosystem may disappear or suffer high anthropogenic disturbances. The aim of the study was to evaluate the structure and distribution of woody species, after the implantation of artificial drainage channels in campo de murundus, in plots near and distant of the drains in the soil. We sampled woody individuals with ≥ 3 cm diameter at the base, and established 20 permanent plots of 20×50 m, 10 of which were between 0-20 m of the drains (edge) and 10 between 150-200 m distant from the drains (interior), totaling two hectares of survey. We recorded 47 species with total density of 230.5 ind.ha-1 and total basal area of 1.331 m2 ha-1. The diversity index of species was H’ = 3.18. We recorded higher density and basal area in the edge, and differential distribution and occupation of woody species in the microrelief of the murundus. This provides us strong evidence that the drains have altered the vegetation structure, especially in the edge of the remnant campos de murundus turning the vegetation woodier and denser.